Neurological Nuance: Sporadic Burkitt's Lymphoma Presenting with Guillain–Barre Syndrome - Bouattour, Nadia; Kamoun, Fatma; Charfi, Slim; Nsir, Siham Ben; Bouchaala, Wafa; Boudawara, Tahya; Triki, Chahnez (Journal of Pediatric Neurology, 2020)
Burkitt's lymphoma (BL) is a high-grade mature B cell neoplasm. Primary lymphoma of the central nervous system (CNS) is very rare. In contrast, BL can be localized in any part of the body and may spread to the CNS. Peripheral nervous system impairment caused by BL has been thoroughly described. However, Guillain–Barre syndrome (GBS) does not commonly appear as an initial manifestation of BL. We presented the case of a young child with sporadic BL with neuromeningeal involvement and spinal cord compression whose first clinical manifestation was the appearance of GBS. Lymphoma should be taken into account, especially in children presenting with the clinical features of acute polyradiculoneuropathy.
Keywords: Guillain–Barre's syndrome; Burkitt's lymphoma; lymphoma; neurology